Real time ultrasound evaluation of changes in follicular populations during oestrous cycle in buffalo - Manik, R S; Singla, S K; Palta, P; Madan, M L (The Indian Journal of Animal Sciences, 2012)
Changes in ovarian follicular populations during oestrous cycle were examined by real time ultrasonography in buffaloes. The endpoints used were number of follicles 3-4 mm, 5-6 mm, 7-10 mm, =11 mm and the diameters of the largest and the second largest follicles, between day 0 and day 15 of oestrous cycle. The profile of the diameter of the second largest, but not the largest follicle was bimodal. There was a significant difference among different days in the diameters of both the largest and the second largest follicle. There was a significant difference in the numbers of follicles 5-6 mm and 7-10 mm in diameter but not in the numbers of follicles 3-4 mm and 11 mm, and the total number of follicles 3 mm in diameter among different days. Our results suggest that the follicular populations exhibit dynamic changes during oestrous cycle in buffaloes.